Deskripsi ulang rayap tanah (Subulitermes-branch): Oriensubulitermes inanis (Haviland) (Termitidae: Nasutitermitinae) di Indonesia - Syaukani, Syaukani; Husni, Husni; Alfizar, Alfizar; Kesumawati, Elly; Novita, Novita; Rusdiana, Siti; Muarrif, Samsul; Pribadi, Teguh (Perhimpunan Entomologi Indonesia, 2019)
Oriensubulitermes inanis (Haviland) is one of the endemic termites in the Oriental Region and plays a very important role in the decomposition process in tropical forests. This study aims to redescribe O. inanis from Indonesia. Termite were collected by adopting a Standized Sampling Protocol (Jones & Eggketon 2000) and final taxonomic confirmation were conducted at the Natural History Museum UK) and Florida University (USA). We found 21 colonies of O. inanis from various habitats and altitudes in Indonesia. Distribution of O. inanis is often correlated with biodiversity status in tropical forests. Worker caste mandible provides the most useful character for the description of O. inanis. In Southeast Asia, this rare species is restricted and can be found only in the Malay Peninsula, Borneo and Sumatra, and absence from Java. Decayed wood, base of tree trunks, and other termite nests (epigeal mounds) are selected media used to construct their nests. Limited population number in a colony, restricted alates flying ability, and secretive nest habitats are thought to influence the distribution of O. inanis in Indonesia.